A comprehensive review on the phytochemistry, pharmacological, ethnobotany, and traditional uses of Paeonia species - Sunil Kumar; Kshirod Kumar Ratha; Meda Mruthyumjaya Rao; Rabinarayan Acharya (Shahrekord University of Medical Sciences, 2023)
Since ancient times, people have used medicinal plants as a source of medications to treat and prevent diseases. Paeonia species are important therapeutic plants in Ayurvedic, Unani, and Traditional Chinese Medicine. This study aims to provide updated information on the ethnobotany, phytochemistry, and pharmacological activities of Paeonia species discovered until now. Using the keywords "Paeonia", "geographical distribution", "ethnopharmacology and traditional values", "phytochemistry", "antioxidant", "anti-inflammatory", "antimicrobial", "cardiovascular diseases", and "anticancerous properties", the published reports from 2001 to 2022 were retrieved using Google Scholar, Science Direct, PubMed, and Scopus databases. A total of 156 published articles were studied after meeting the qualifying criteria. Out of these, 52 articles were studied for phytochemistry, ethnopharmacological and traditional uses. Paeonia emodi is used to treat hypertension, asthma, convulsions, epilepsy, bronchitis, ascites, uterine abnormalities, and a variety of skin ailments. Bioactive compounds like triterpenes, monoterpene glucosides, phenols, tannins, emodinol, benzoic acid, paeonin A and B, steroids, several secondary metabolites like paeoniflorin and paeonol, and several minerals are abundant in the Paeonia species. In recent studies, Paeonia emodi has been shown to possess pharmacological properties like antioxidant, antibacterial, anti-inflammatory, insecticidal, and anti-tumor activities. Convincing data supports the traditional ethnomedicinal claims of the plant; the abundant phytocompounds of the plant are attributed to its broad spectrum of pharmacological activities. In order to understand the molecular mechanisms underlying the action of the bioactive ingredients in drug development processes and to investigate their potential at the clinical level, more research is required.